HIV and hepatitis C virus infections among hanka injection drug users in central Ukraine: a cross-sectional survey - Slobodyanyuk Pavel; Chandler Susan D; Zezyulin Olexandr O; Qian Han-Zhu; Soldyshev Ruslan; Dumchev Kostyantyn V; Moroz Larisa; Schumacher Joseph E (BMC, 2009)
Abstract Background Ukraine has experienced an increase in injection drug use since the 1990s. An increase in HIV and hepatitis C virus infections has followed, but not measures of prevalence and risk factors. The purposes of this study are to estimate the prevalence of HIV, HCV, and co-infection among injection drug users (IDUs) in central Ukraine and to describe risk factors for HIV and HCV. Methods A sample of 315 IDUs was recruited using snowball sampling for a structured risk interview and HIV/HCV testing (81.9% male, 42% single, average age 28.9 years [range = 18 to 55]). Results HIV and HCV antibodies were detected in 14.0% and 73.0%, respectively, and 12.1% were seropositive for both infections. The most commonly used drug was hanka, home-made from poppy straw and often mixed with other substances including dimedrol, diazepines, and hypnotics. The average period of injecting was 8.5 years; 62.5% reported past-year sharing needles or injection equipment, and 8.0% shared with a known HIV-positive person. More than half (51.1%) reported multiple sexual partners, 12.9% buying or selling sex, and 10.5% exchanging sex and drugs in the past year. Those who shared with HIV positive partners were 3.4 times more likely to be HIV positive than those who did not. Those who front- or back-loaded were 4 times more likely to be HCV positive than those who did not. Conclusion Harm reduction, addiction treatment and HIV prevention programs should address risk factors to stop further spread of both HIV and HCV among IDUs and to the general population in central Ukraine.